Effectiveness of training program as perceived by workers at commercial bank, cooperation bank and community bank in Jengka, Pahang / Norfazura Mustafa and Wan Nurzatilyumni Wan Mohd Tarmizi - Mustafa, Norfazura; Wan Mohd Tarmizi, Wan Nurzatilyumni (2009)
This study is to find out whether the training program that the workers had attended really is effective and to identify the employees or bankers from commercial bank, cooperation bank and community bank in Jengka Pahang perceptions about the effectiveness of their training program. Questionnaires have been distributed to 40 respondents from these banks and 29 questionnaires were collected from these respondents. Data was analyzed using the SPSS version 16.0. From this study, it showed that most of the respondents agree that attending the training program will improve their skills, behaviors and enhanced their productivity. Moreover, based on the findings, there were some recommendations to the company such as provide the appropriate training method to the trainee, provide some reinforcement when the employees learn, evaluate the employees job performance, establish continuing learning programs based upon the collective experience of veteran workers in the company and provide the comprehensive training especially for the new employees.